Learning strategies: perceptions on using songs and movies in learning a foreign language - Abdul Razak, Adlina Amani; Mohd Basari, Shahrul Nizam (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
In the current era, movies and songs are very common in our daily lives; hence language learners should utilize these strategies in acquiring a new language, especially when their benefits and advantages have been highlighted in many studies. However, there are still some limitations that are faced by instructors and learners when integrating songs and movies in language learning. Thus, this paper aims to explore i) the perceptions of IIUM students on the integration of movies in foreign language learning and ii) the perceptions of IIUM students on the integration of songs in foreign language learning. This study employed the quantitative research design. It used online questionnaires which were analysed using descriptive statistics. From the findings, it is found out that the majority of the students have positive perceptions towards the integration of both songs and movies as a strategy in learning a foreign language. Upon completing the paper, the main limitations that were faced by the researcher were to get the targeted respondents to answer the questionnaires and also time constraint.